Analisa Pengaruh Diameter Impeller Terhadap Kapasitas Dan Penurunan Tekanan Blower Sentrifugal - K. Umurani; Rahmatullah Rahmatullah; Fariz Aulia Rachman (Rekayasa Material, Manufaktur dan Energi, 2020)
Blower is a device used to increase or increase the pressure of air or gas that will be flowed in a particular room as well as suctioning certain air or gas where the Blower produces a relatively high pressure ratio with a greater volume of gas flow. At present the role of the Blower has begun to be widely used, especially in the engineering field, where the Blower role was created to facilitate the process of air exhaust. The blower itself is a producer of air movement which is generally used for ventilation. Blowers consist of several types, namely Axial Blowers and Centrifugal Blowers. Blowers have one component, namely Impeller. To determine the right diameter of the impeller, a performance test on centrifugal blowers with different variations in the size of the impeller diameter is needed, such as an anemometer, wattmeter and tachometer, and the impeller diameters are 180 mm, 190 mm and 200 mm with a rotational speed of 1500 rpm. The results obtained from testing on the diameter of the 200 mm impeller obtained the highest efficiency with a value of 0.0086%. The maximum air velocity is found in the diameter of the impeller with a size of 200 mm which is equal to 19.82 km / h. Then, the maximum pressure drop (∆p) is found at the diameter of the impeller with a size of 200 mm and 190 mm with the same result which is 136,206954 Pa. Then followed by the largest capacity value (Q) found in the variation of the diameter of the impeller with a size of 200 mm that is equal to 118.92 m3 / h. And the largest motor power is found in variations in the diameter of the impeller with a size of 200 mm that is equal to 62.85 W.